2017
DOI: 10.1097/md.0000000000006043
|View full text |Cite
|
Sign up to set email alerts
|

Can tranexamic acid reduce blood loss in cervical laminectomy with lateral mass screw fixation and bone grafting

Abstract: To assess the safety and efficacy of tranexamic acid (TXA) for decreasing perioperative blood loss in cervical laminectomy with lateral mass screw fixation and bone grafting (CLF), in which all surgical procedures are identical.From November 2014 to April 2016, we performed a retrospective comparative analysis of 119 patients with multilevel cervical spondylotic myelopathy who had undergone a CLF from C3 to C6 in our center. All surgeries were performed on the patients using a consistent, standard procedure. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 31 publications
4
35
3
Order By: Relevance
“…The intravenous application of TXA has been confirmed as effectively decreasing blood loss and transfusion requirement in spinal surgery [ 6 , 7 ]. Recently, topical TXA is widely established in hip and knee arthroplasty and successfully reduced postoperative blood loss and blood transfusion requirements [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intravenous application of TXA has been confirmed as effectively decreasing blood loss and transfusion requirement in spinal surgery [ 6 , 7 ]. Recently, topical TXA is widely established in hip and knee arthroplasty and successfully reduced postoperative blood loss and blood transfusion requirements [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated how preoperative intravenous administration of tranexamic acid (TXA) (FS) contributed to hemostasis and reduced postoperative blood loss following spinal surgery [ Table 4 ]. [ 2 7 10 13 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…(2017) documented TXA effectively promoted hemostasis for 73 patients undergoing cervical laminectomy/lateral mass screw fusion vs. 46 controls; TXA contributed to decreased intraoperative blood loss (179.66 vs. 269.13), postoperative blood loss (108.08 and 132.83), total blood loss (287.74 vs. 401.96), without any major thromboembolic/other complications. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…RCDI is more frequent in patients infected with the 027 strain than in those infected with non-027 strains (P < 0.001). Besides, the clinical cure rate has been reported to be lower in 027-infected patients than in those with non- Long persistence/protection of C. difficile [36,[42][43][44][45][46] Accumulation of spores Reduced susceptibility to antibiotics [45,47] SlpA (S-layer protein A)…”
Section: Ribotypes Associated With Relapse or Reinfectionmentioning
confidence: 99%